Eksistensi Tari Sakral Gambuh di Desa Anturan Kecamatan Buleleng dalam Perspektif Ilmu Komunikasi - Kristiawan, Putu Bayu; Gara, I Wayan; Saputra, Putu Agus Panca (Prabha Vidya, 2024)
This research uses several theoretical bases, including: Communication Science Theory, Structural Functional Theory put forward by Talcott Parsons, and Symbolic Interaction Theory put forward by George Herbert Mead. The methods used to collect data in this research include: observation method, interview method, library method, and documentation method. The descriptive analysis method is used to analyze the data that has been collected, using several steps of data collection, data reduction, data presentation, and data conclusion. Data analysis in the results of this research shows: The history of the development of the implementation of the sacred gambuh dance tradition and the forms of its implementation. The function of implementing the sacred gambuh dance tradition in Anturan Village from a Hindu communication science perspective. The meaning contained in the performance of the sacred gambuh dance tradition is seen from the perspective of Hindu communication science, namely the meaning of harmony, the meaning of ethics, and the meaning of education.